A garota das flores (1972): uma análise da questão nacional no cinema da Coreia do Norte - Pinheiro, Gabriel da Silva (Universidade Federal de São Carlos, 2023)
이 연구는 1972년에 제작된 북한 영화인 꽃 소녀를 분석하여 북한의 국가적 문제와 영화 간의 상호 작용을 탐구합니다. 또한 이 연구에서는 국가 내 영화 발전의 역사적 과정을 조망합니다. 북한 영화, 역사 및 정치, 그리고 소련과 중국 같은 다른 영화의 미학적 영향 사이의 관계를 조사합니다. 꽃 소녀 영화의 분석은 영화 작품과 그 역사적 및 정치적 맥락 간의 대화를 촉진합니다. 이는 주인공인 꽃분에 중점을 둔 국가적 역사적 애러를 강조합니다.

The work analyzes the North Korean film The Flower Girl from 1972 to explore the interactions between national issues and cinema in North Korea. Additionally, a historical mapping of the development of cinema in the country is conducted. The relationships between cinema, North Korean history and politics, and the aesthetic influences of cinemas such as those of the Soviet Union and China are examined. The analysis of the film The Flower Girl promotes a dialogue between the cinematic work and its historical and political context. It emphasizes the use of the national historical allegory focused on the main character, Koppun.

El trabajo analiza la película norcoreana La Florista de 1972 para explorar las interacciones entre las cuestiones nacionales y el cine en Corea del Norte. Además, se realiza un mapeo histórico del desarrollo del cine en el país. Se examinan las relaciones entre el cine, la historia y la política de Corea del Norte y las influencias estéticas de cines como el de la Unión Soviética y China. El análisis de la película La Florista promueve un diálogo entre la obra cinematográfica y su contexto histórico y político. Se enfatiza el uso de la alegoría histórica nacional centrada en el personaje principal, Koppun.
The flower girl (1972): an analysis of the national question in north korean cinema
La florista (1972): un análisis de la cuestión nacional en el cine de Corea del Norte
Keywords: Cinema; Coreia do norte; A garota das flores; Film; North korea; The flower girl; Cine; Corea del norte; La florista; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA